Rethinking Entrepreneurship for Sustainability: An Application of the Spirit, Body and Soul (SBS) Model to Developing Economies - Muritala AWODUN, Ph.D.; Lukman ADAM, Ph.D. (Journal of World Economy, 2025)
Entrepreneurship has truly driven the developed economies to growth and development, and the case of developing economies cannot be different. Despite the huge population and natural resource dominance of these economies, development in terms of infrastructure and growth has been distorted. This paper takes a critical look at the understanding of the concept of entrepreneurship with the aim of ensuring sustainable entrepreneurship in the developing economies. To achieve this, the paper examines the SBS model of entrepreneurship relating its applicability to the developing economies for there to be any form of sustainable development. Following the lead of scholars such as Baumol (1968); Dees (2001); Coyne & Leeson (2004); Austin et.al. (2006); Baumol & Strom (2007) Desai & Acs (2007); Schumpeter (2008); Boettke & Coyne (2009); Kirzner (2009); Simons et. al. (2011); Desai (2013); Lucas & Fuller (2015); Hippel (2017), the paper adopted the approach of giving ‘life’ to entrepreneurship through the application of the spirit, body and soul (SBS) model, where entrepreneurship or being enterprising is likened to the human ‘body’, entrepreneurial to the ‘spirit’, and entrepreneurialism to the ‘soul’ with the submission that sustainable entrepreneurship must connect the trio in the entrepreneur who is the ‘person’ that creates the product and the enterprise, as the ‘business’ that work in partnership to create sustainable development.